Kehidupan Sosial Ekonomi Petani Jeruk di Kenagarian Siguntur Kecamatan Sitiung Kabupaten Dharmasraya (1985-2020) - Tesa Rosalita; Azmi Fitrisia (Jurnal Kronologi, 2022)
This study aims to reveal the dynamics of citrus plantations in Siguntur and understand the economic condition of citrus farmers in Siguntur, Sitiung District, Dharmasraya Regency in 1985-2020. The method used in this test is the historical method which consists of four stages, namely heuristics, source analysis, interpretation, and historiography. The results of the study reveal that the dynamics of the socio-economic life of citrus farmers have continued to develop since 1985-2020, this is evidenced by the increase in citrus production from 1990-2000, but a decline in 2004-2012 due to seasonal pest diseases that attack citrus plants. Citrus production increased again in 2014-2019 with the highest production in 2016. Citrus plantations have an impact on the lives of farmers in the social and economic fields, it can be seen in terms of increased community income, education is getting attention, property ownership such as many who have renovated houses and bought vehicles, changes in attitude and behavior as well as position and honor in society that are starting to be noticed. Keywords: Development, Socio-Economic, Orange Farmers